A Review on Glycerol-Based Drilling Fluids and Glycerine as a Drilling Fluid Additive (Rudarsko-geološko-naftni zbornik, 2024)
A significant increase of energy demands all over the world and production decline from available oil and gas reservoirs have led the industry to invest in major offshore petroleum resources. However, drilling operations in offshore environments are usually restricted by environmental constraints. Therefore, recent studies are devoted to the development of environmentally compatible fluids with adequate technical properties. Glycerine is a non-toxic, lubricating, colorless, odorless substance with a higher density than water. Due to the properties of glycerine, it can be used as the base of drilling fluid to formulate synthetic-based fluids. This research aimed to review the studies on the applications of glycerine in the composition of drilling fluid. Based on the results, glycerine-based fluids can be considered as an environmentally compatible fluid with sufficient technical properties to replace other drilling fluids. However, there is a lack of experimental studies on the glycerine fluid properties for a reliable decision. For the application of glycerine fluids, an economic feasibility study is mandatory for both pure and crude glycerine. Also, the thermal stability of glycerine fluids is an important aspect, which should be covered in future research studies.